2021
DOI: 10.3390/agronomy11040744
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Compounds in Essential Oil of Amomum tsaoko Seed and Fruit Morphological Characteristics, Geographical Conditions, Locality of Growth

Abstract: Amomum tsaoko is a perennial herb belonging to Zingiberaceae. Its dried ripe fruit is an important food additive, spice and materia medicai in Southeast Asia. For hundreds of years of cultivation, morphological variations have existed. The essential oil is one of the major active products of the A. tsaoko fruit and seed. In this study, we collected 12 populations in Yunnan province, and the correlation analysis of compounds was focused on the essential oil of A. tsaoko seed and its fruit morphological characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The classification results of origin are better than those of fruit shape, which is a consistent classification trend for almost all classifiers. A previous result showed that morphological characteristics of fruit shape and seeds correlated with chemical diversity in L. tsaoko essential oil, in contrast to origin differences, which were important factors influencing the compositional characteristics in L. tsaoko essential oil (Li et al, 2021), in agreement with the results of the present study.…”
Section: Evaluation Of the Modelsupporting
confidence: 93%
See 2 more Smart Citations
“…The classification results of origin are better than those of fruit shape, which is a consistent classification trend for almost all classifiers. A previous result showed that morphological characteristics of fruit shape and seeds correlated with chemical diversity in L. tsaoko essential oil, in contrast to origin differences, which were important factors influencing the compositional characteristics in L. tsaoko essential oil (Li et al, 2021), in agreement with the results of the present study.…”
Section: Evaluation Of the Modelsupporting
confidence: 93%
“…Normally, when after planting 3 years L. tsaoko begins to bear fruit, it also can be harvested for about 20 years. Therefore, it has become a precious commercial crop in the remote mountainous areas of Yunnan province and an important way to fight poverty in Yunnan province (Li et al., 2021). For L. tsaoko , the differences among populations are greater than the differences within populations, as well as the differences in altitude similarly influence its quality; the higher the altitude, the more beneficial the biomass accumulation is (Li et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a hot pot, a typical Chinese dish, A. tsao-ko is an indispensable condiment ( Jia et al, 2020 ). It is recorded in the compendium of Materia Medica that A. tsao-ko tastes spicy, warm and belongs to the spleen and stomach meridian ( Li et al, 2021 , Shi et al, 2021 , Wei et al, 2021 ). A large number of previous studies have shown that A. tsao-ko has multiple pharmacological effects such as sedative, antibacterial and immunity enhancement, and its active substance is mainly volatile essential oil ( Qin et al, 2021 , Liu et al, 2021 , Sabulal and Baby, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of alcoholic extracts of some Amomum species revealed the presence of various phytoconstituents, including flavonoids, carbohydrates, anthocyanin, tannins, phenols, alkaloids, and steroids (Konappa et al, 2020). Li et al reported that Amomum tsao-ko is rich in a variety of chemical components of proteins, phenolic compounds, tannins, organic acids, saponins, flavonoids, anthraquinone, coumarin, lactones, steroids, terpenoids, volatile oil, anthocyanins, and so on (Li et al, 2021). As tannin, a wide group of water-soluble polyphenolics, and alkaloid possess anti-nutritional and anti-feed properties (Mueller-Harvey, 2006;Itkin et al, 2013), low availability of these compounds indicated high tissue quality of both Amomum species.…”
Section: Proximate Composition Analysismentioning
confidence: 99%